ENSO combination mode and its influence on seasonal precipitation over southern China simulated by ECHAM5/MPI-OM - Shengjie YI; Fei ZHENG; Hao LUO (Atmospheric and Oceanic Science Letters, 2019)
Recent studies show that a combination mode (C-mode) represents the seasonally modulated dynamics of ENSO, which plays an important role in maintaining the western North Pacific anomalous anticyclone. This C-mode could obviously influence the East Asian climate, especially since the contribution of ENSO to southern China’s precipitation has weakened since the late 1990s. This paper evaluates whether the C-mode and its influences on precipitation over southern China can be realistically described by the climate model ECHAM5/MPI-OM. The authors find that the model is able to reproduce the spatial and temporal variability of the C-mode and the asymmetric responses of air–sea variations in the tropical Pacific. The model also reveals the observed significant effects of the C-mode on the wintertime and springtime rainfall over southern China during El Niño events. The findings have implications for ECHAM5/MPI-OM being a valuable tool for simulating and predicting the C-mode-related seasonal precipitation over southern China.